A community of writers : Paul Engle and the Iowa Writers' Workshop - Dana, Robert, 1929-2010 (University of Iowa Press, 1999)
With these words, written long before his Iowa Writers' Workshop became world famous, much imitated, and academically rich, Paul Engle captured the spirit behind his beloved workshop. Now, in this collection of essays by and about those writers who shared the energetic early years, Robert Dana presents a dynamic, informative tribute to Engle and his world. The book's three sections mingle myth and history with style and grace and no small amount of humor. The beginning essays are given over to memories of Paul Engle in his heyday. The second group focuses particularly on those teachers &